Restaurant Reservation System - Ong, Jun Kit (2021)
Many businesses have digitally transformed their business model with modern digital technology to give themselves a competitive advantage in the market. In order to catch up the business digitalization trends, many catering industries have begun to run their reservation management online. On the contrary, some restaurants use traditional and paper-based approach in table booking management, which is inefficient and ineffective. Furthermore, customers may face some challenges in making a reservation with the restaurant staff without a proper channel. Hence, in this project, web-based restaurant reservation system is developed to solve the problems faced both customers and restaurateurs. Prototyping methodology was implemented in web-based system development. This methodology consists of four phases such as requirement gathering and analysis, quick design, building prototype, customer evaluation and engineer product. Prototype was built and gone through three iterations. The new features were added in refining prototype phase in each iteration. In the first iteration, the user interface design and web-pages navigation were designed, sketched, and developed. In second iteration, backend of the system such as SQL database connection, CRUD functionalities, and essential features. In third iteration, all the functionalities derived from functional requirement and scope of this project were developed. In conclusion, web-based restaurant reservation was developed to aid the restaurateurs to manage the incoming reservation made by their customers without any paper-based approach. With this system, restaurateurs could manage food pre-ordered by customers, restaurant menu, view report and export reservation list and report. Furthermore, customers, also known as diners could make a reservation as well as modify and cancel reservation with ease. Other than table booking feature, customers could also pre-order foods for the reservation and modify it in effective and timesaving way. All the functionalities and features in this system were tested with the designed requirement-based test cases. All the test cases were executed and passed. Therefore, all the functional and non-functional requirements were fulfilled and the project objectives were achieved as well